Contraceptive and prevention methods of transmission/reinfection of the virus among patients with HIV/aids - Cunha, Gilmara Holanda da; Galvão, Marli Teresinha Gimeniz (Rev Rene, 2011)
The aim of this study was to identify methods of contraception and prevention of transmission/reinfection of the virus in patients with HIV/AIDS attending a university hospital in Fortaleza/CE/BR. It was used cross-sectional as well as descriptive methods, with application of questionnaire for 51 patients between August 2006 and January 2007. Most patients were male, aged 31 — 40 years, married, of the heterosexual exposure category and with serodiscordant partners. There was use of condoms regularly (72.5%), sexual abstinence (4.0%), condom irregularly associated with oral and injectables contraceptives (4.0%) and tubal ligation (11.7%). By Fisher’s exact test, condom use was significantly higher among men (p=0.0002). Change of sexual activity after diagnosis occurred in 80.4% of the individuals. The findings suggest the need of orientation for the regular use of male and female condom, because this can prevent pregnancy and sexually transmitted diseases.